Production of breakfast cereals mixed with dried fruits a plant design - Lopez, Marlene V. (College of Engineering, 1998)
Product: Breakfast cereals mixed with dried fruits -- Plant location: Barangay Banaba, Industrial Zone I, Batangas City -- Production capacity: 875,000 kg/year -- Proposed selling price: Php 85.00 per 300 grams -- Prevailing market price of local plain corn flakes: Php 70.75 per 300 grams -- Prevailing market price of imported cereals with fruits: Php 152.70 per 500 grams -- Annual gross sales: Php 273,979,216.15 (average for the first five years) -- Net profit: Php 86,764,652.75 (average for the first five years) -- Total capital investment: Php 67,099,353.59 -- Fixed capital investment: Php 39,631,882.60 -- Working capital: Php 27,467,530.99 -- Payback period: 0.7634 year (after taxes) -- Break-eve price: Php44.239 per 300 grams -- Break-even volume: 455,000 kg per year -- Return on investment: 129.31%